TEORI DAN MODEL PENGEMBANGAN SDM - Fania Halisa Lisbeth; Revalya Rahma Putri; Sifa Silvia; Machdum Bachtiar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Human resource development (HRD) is a strategic, planned, and sustainable effort to enhance individual quality in terms of knowledge, skills, attitudes, and work behavior. This article aims to examine the general concepts of HRD evaluation and development, HRD development models, and strategic challenges in their implementation. HRD cannot be separated from the evaluation process, as evaluation measures the effectiveness of training programs and ensures tangible performance improvements. Evaluation models, such as Kirkpatrick's framework, are widely used to assess program success. Additionally, various HR planning models proposed by experts like Mondy, Noe, and Cascio highlight the importance of integrating organizational strategy with workforce management. In practice, HRD faces numerous challenges, both external—such as technological advancements and globalization—and internal, including budget constraints and individual resistance to change. Therefore, appropriate implementation strategies, such as needs-based training and cross-sector collaboration, are key to success. Through systematic integration of planning, execution, and evaluation, HRD can sustainably enhance organizational competitiveness.